Effect of 0.2% Chlorhexidine Gel on Frequency of Dry Socket Following Mandibular Third Molar Surgery: A Double-Blind Clinical Trial Clinical Trial - Baratollah Shaban; Hamid Reza Azimi; Hani Naderi; Anooshe Janani; Mohammad Javad Zarrabi; AmirHossein Nejat (Mashhad University of Medical Sciences, 2014)
Introduction: Alveolar osteitis (AO) is one of the most common postoperative complications after third molar surgery. Various techniques have been used to reduce the risk of AO. The aim of the current study was to evaluate the effect of Chlorhexidine (CHX) bioadhesive gel in preventing the development of AO. Methods: Patients with bilateral impacted mandibular third molars underwent surgical extraction of both teeth. One socket was randomly received CHX gel and the contralateral socket served as the control. The outcome variable was development of AO and the CHX gel application was the predictor variable. Data were analyzed using chi-square test with the confidence interval of 95%. Results: 41 patients (27 females and 14 males) with mean age of 24.15 ± 5.02 years underwent 82 surgeries. Total of 11 sockets (13.41%) developed AO. The frequency of AO in CHX gel (2 cases, 4.87%) side was significantly lower than control (9 cases, 21.95%) side (P-value < 0.05). No side effects observed following CHX gel application. Conclusion: Application of CHX gel could be an effective approach to reduce the risk of developing AO following mandibular third molar surgery.